2022
DOI: 10.3390/jcm11040963
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxygen Extraction by Pulmonary Rehabilitation Improves Exercise Tolerance and Ventilatory Efficiency in Advanced Chronic Obstructive Pulmonary Disease

Abstract: Background: In cardiopulmonary exercise testing (CPET), oxygen uptake (V’O2) is calculated using the product of minute ventilation (V’E) and the difference between inspiratory and expiratory O2 concentrations (ΔFO2). However, little is known about the response of ΔFO2 to pulmonary rehabilitation (PR). The aim of the present study was (1) to investigate whether PR increases peak V’O2, based on whether ΔFO2 or V’E at peak exercise increase after PR, and (2) to investigate whether an improvement in ΔFO2 correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Pulmonary rehabilitation had been asserted to assist with enhancing oxygen extraction, improving exercise tolerance and ventilatory efficiency in studies involving COPD patients. 22 We posit that rehabilitation had been helpful in improving the functional outcome of our subjects as well. At discharge, most (65.2%) had achieved independence in basic ADLs, freed of supplemental oxygen use.…”
Section: Discussionmentioning
confidence: 86%
“…Pulmonary rehabilitation had been asserted to assist with enhancing oxygen extraction, improving exercise tolerance and ventilatory efficiency in studies involving COPD patients. 22 We posit that rehabilitation had been helpful in improving the functional outcome of our subjects as well. At discharge, most (65.2%) had achieved independence in basic ADLs, freed of supplemental oxygen use.…”
Section: Discussionmentioning
confidence: 86%
“…To date, the studies that have examined the utility of assessing ventilatory efficiency in the evaluation of COPD patients with dyspnea have been relatively few with small numbers of participants. 28,32,33,[37][38][39][40][41][42][43] Phillips and colleagues from the Canadian Research Group Canadian study of Chronic Obstructive Lung Disease (CanCOLD) were well positioned to address this question. The consortium of 9 respiratory research centers in Canada has assembled a cross-sectional cohort of Canadians over 40 years old who have undergone a battery of tests including pulmonary function testing, exercise tolerance testing, computed tomography (CT) scanning, modified Medical Research Council (mMRC) breathlessness and COPD assessment test scoring.…”
Section: Measurements and Main Resultsmentioning
confidence: 99%
“…Previously, data demonstrated that exercise training improves peak oxygen consumption in heart failure patients by increasing the cardiac output with an unchanged average arteriovenous oxygen difference, suggesting the crucial role of blood flow distribution towards the periphery [17]. In this Special Issue, Miyazaki and colleagues [18] deeply investigated exertional pathophysiology conditions, specifically evaluating oxygen extraction measurements following rehabilitation in chronic obstructive pulmonary patients. The same intriguing comparison between pulmonary and cardiac patients' pathophysiologies was also performed by evaluating different parameters, such as minute ventilation for a given carbon dioxide production, which is known to also have a relevant prognostic power in heart failure patients [19].…”
Section: Protocolsmentioning
confidence: 99%